1995
DOI: 10.1079/bjn19950141
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation, prostacyclin and thromboxane A2in pigs depleted of vitamin E and selenium and supplemented with linseed oil

Abstract: In a 2 x 2 balanced factorial experiment the biochemical effects on pigs of two dietary factors were investigated. The first factor was a-tocopherol and Se supplementation and the second factor was supplementation with a-tocopherol-stripped linseed oil. In pigs fed on diets depleted of a-tocopherol and Se, increases in concentrations of markers of Lipid peroxidation (4hydroxynonenal and hexanal) were observed. However, skeletal myopathy was only observed in those pigs fed on diets depleted of atocopherol and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 14 publications
(9 reference statements)
1
3
0
3
Order By: Relevance
“…Table 3 also shows that the increase in n− 3 fatty acids was accompanied by a corresponding decrease (p ≤ 0.05) in arachidonic acid. This is consistent with other authors who reported a decrease in arachidonic acid in heart and supraspinatus muscles, but not in longissimus muscle when linseed oil was fed to pigs (Nolan, Kennedy, Blanchflower, & Kennedy, 1995). These authors suggested that this decrease was probably the result of peroxidation of arachidonic acid.…”
Section: Effect Of Dietary Linseed Oil and Its Combinations With Olivsupporting
confidence: 89%
See 1 more Smart Citation
“…Table 3 also shows that the increase in n− 3 fatty acids was accompanied by a corresponding decrease (p ≤ 0.05) in arachidonic acid. This is consistent with other authors who reported a decrease in arachidonic acid in heart and supraspinatus muscles, but not in longissimus muscle when linseed oil was fed to pigs (Nolan, Kennedy, Blanchflower, & Kennedy, 1995). These authors suggested that this decrease was probably the result of peroxidation of arachidonic acid.…”
Section: Effect Of Dietary Linseed Oil and Its Combinations With Olivsupporting
confidence: 89%
“…However, the extent of lipid oxidation differed (p≤0.05) between the dietary treatments, the increase being higher for the L group that had been dietary supplemented with 3% linseed oil, which is rich in α-linolenic acid. Group S that had been dietary supplemented with sunflower oil, which is rich in linoleic acid, presented MDA values lower (p≤0.05) than those of the L group at all time points, probably due to the fact that α-linolenic acid is more prone to oxidation than linoleic acid (Nolan et al, 1995). Τhe LOL5 group presented MDA values lower (p≤0.05) than those of the (S) group but higher (p≤0.05) than those of the LOL10 group, which in turn, presented MDA values higher (p≤0.05) than those of the LE group, at all storage times.…”
Section: Effect Of Dietary Linseed Oil and Its Combinations With Olivmentioning
confidence: 46%
“…The desaturase and elongase activities seem to be more focused on the synthesis of n-3 instead of on the synthesis of n-6 fatty acids metabolites. On the contrary, Nolan et al (1995) did not report a decrease in arachidonic acid content in the longissimus muscle by feeding linseed oil. Sheard et al (2000) and Hoz et al (2003) studied the influence of linseed-rich test diet on fatty acid content in meat.…”
Section: Resultsmentioning
confidence: 88%
“…Combined selenium and vitamin E deficiency has also resulted in unfavourable lipid profiles in animal models (Mazur et al, 1996). A protective effect of selenium and vitamin E against lipid peroxidation has been observed and a possible mechanism of action through GPx or selenoprotein P has been proposed (Awad et al, 1994;Burk et al, 1995;Nolan et al, 1995). Results of the NPC trial (Clark et al, 1996) suggest an involvement of vitamin E, in that subjects ranking below the median plasma a-tocopherol concentration at entry to the study showed higher rates of subsequent carcinomas and greater apparent protective effects of selenium supplementation during the course of the trial ).…”
Section: Interactions Of Selenium With Other Nutrients and Drugsmentioning
confidence: 99%